2003
DOI: 10.1021/jm030868a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, in Vitro Evaluation, and Antileishmanial Activity of Water-Soluble Prodrugs of Buparvaquone

Abstract: Water-soluble phosphate prodrugs of buparvaquone (1), containing a hydroxynaphthoquinone structure, were synthesized and evaluated in vitro for improved topical and oral drug delivery against cutaneous and visceral leishmaniasis. The successfull prodrug synthesis involved a strong base; e.g., sodium hydride. Buparvaquone-3-phosphate (4a) and 3-phosphonooxymethylbuparvaquone (4b) prodrugs possessed significantly higher aqueous solubilities (>3.5 mg/mL) than the parent drug (e0.03 µg/mL) over a pH range of 3.0-7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
67
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(68 citation statements)
references
References 37 publications
0
67
1
Order By: Relevance
“…Buparvaquone is a hydroxynaphthoquinone derivative which cannot diffuse through skin contrary to its prodrug formulation (Mantyla et al, 2004). Quite few reports of the treatment effect of this compound against leishmaniasis are available (Garnier et al, 2007).…”
Section: Buparvaquonementioning
confidence: 99%
“…Buparvaquone is a hydroxynaphthoquinone derivative which cannot diffuse through skin contrary to its prodrug formulation (Mantyla et al, 2004). Quite few reports of the treatment effect of this compound against leishmaniasis are available (Garnier et al, 2007).…”
Section: Buparvaquonementioning
confidence: 99%
“…The heterocyclic derivatives of -1,4-naphthoquinones have been identified that have potent biological activities towards viral [5], molluscidal [6], malarial [7], leishmanial [8], cancer [9], and bacterial and fungal diseases [10], due to their redox potentials [11].…”
Section: Introductionmentioning
confidence: 99%
“…These findings led to the synthesis of a number of watersoluble phosphate prodrugs such as BPQ-3-phosphate and 3-phosphonooxymethyl-BPQ, whose aqueous solubility is more than 3.5 mg/mL over the pH range of 3.0-7.4. These prodrugs are sufficiently stable in the gastrointestinal tract before their absorption and are rapidly hydrolyzed (t 1/2 = 1.2 and 3.8 min) to the parent compound in the presence of alkaline phosphatases (Mantyla et al, 2004b).…”
Section: Introductionmentioning
confidence: 99%